Audit Manajemen Atas Fungsi Sumber Daya Manusia Pada PT Tjokro Bersaudara Samarindaindo - Danna Solihin, Fransiska Reza Karina Hayuning Mardiana2 (EKONOMIA, 2021)
The purpose of this study is find out and analyze the implementation of human resource audits in the management of Human Resources at PT. Tjokro Bersaudara Samarindaindo has been carried out effectively and efficiently in the fieldThe analytical tool used is a comparative method that is comparing the existing systems and procedures in the company with and conducting a follow-up audit to evaluate the audit findings by asking questions in the form of questionnaires Internal Control Quistionaries.The results of this study indicate that human resource activities at PT. Tjokro Bersaudara Samarindaindo is not running well, this is evidenced by the results of the analysis of human resource activities get a relative value that is not appropriate. The procedure for testing the management control system for the functions of Human Resources planning, recruitment, selection and placement, training and development of employees, occupational safety and health, and layoffs also results in a less appropriate relative value, so that the company's internal control system is poorly implemented.The conclusion of this study in general in terms of the activities of Human Resources that occur in the field at PT Tjokro Bersaudara Samarindaindo is not suitable so that improvements are needed to the existing management control system to facilitate existing activities.